Delivering Beauveria bassiana with electrostatic powder for the control of stored‐product beetles. Issue 8 (22nd February 2017) - Athanassiou, Christos G; Rumbos, Christos I; Sakka, Maria; Potin, Olivier; Storm, Clare; Dillon, Aoife B
Abstract: BACKGROUND: The efficacy of a Beauveria bassiana ‐based formulation (Bb38) with Entostat, an electrostatically charged powder, was investigated as a surface treatment against Cryptolestes ferrugineus, Oryzaephilus surinamensis and Sitophilus granarius adults. In lab bioassays, the efficacy of Bb38 against the aforementioned species was examined on concrete, plywood, steel and ceramic, whereas its residual efficacy against the same species was assessed on concrete and steel in the presence or absence of illumination. Finally, the efficacy of Bb38 against O. surinamensis and S. granarius adults was assessed in a commercial grain storage facility under realistic field conditions. RESULTS: In the lab trials, O. surinamensis and C. ferrugineus were much more susceptible to Bb38 than S. granarius on all types of surfaces. Moreover, Bb38 was, at least for O. surinamensis and C. ferrugineus, as effective as the chemical standard (deltamethrin) for at least 2 months after the application, regardless of the presence or absence of illumination. Finally, in the field trial Bb38 provided a satisfactory level of control against O. surinamensis . CONCLUSION: Bb38 is an effective surface treatment, but its efficacy varies according to the target species, the type of surface and the time post‐application. This is the first published report that examines the efficacy of Bb38 as a surface treatment for wider uses in empty warehouses and related storage facilities. © 2017 Society of Chemical Industry